Changes in the Management of Patients with Crohn's Disease Based on Magnetic Resonance Enterography Patterns - Chinem, Evelyn Sayuri S. (Gastroenterol Res Pract, 2019)
BACKGROUND AND AIMS: Magnetic resonance enterography (MRE) has become an important modality of radiological imaging in the evaluation of Crohn's disease (CD). The aim of this study was to investigate the impact of MRE in the assessment of disease activity and abdominal complications and in the making of therapeutic decisions for patients with CD. METHODS: In a cross-sectional retrospective study, we selected 74 patients with CD who underwent MRE and ileocolonoscopy with an interval between the two exams of up to 30 days between January 2011 and December 2017. We assessed the parameters of the images obtained by MRE and investigated the agreement with the level of disease activity and complications determined by a clinical evaluation, inflammatory biomarkers, and endoscopy, as well as the resulting changes in medical and surgical management. RESULTS: Changes in medical management were detected in 41.9% of patients. Significant changes in medical decisions were observed in individuals with a purely penetrating (P = .012) or a mixed (P = .024) MRE pattern. Patients with normal MRE patterns had a correlation with unchanged medical decisions (P = .001). There were statistically significant agreements between the absence of inflammatory criteria on MRE and remission according to the Harvey and Bradshaw index (HBI) (P = .037), the presence of inflammatory criteria on MRE and positive results for calprotectin (P = .005), and penetrating criteria on MRE and the scoring endoscopic system for Crohn's disease (SES-CD), indicating active disease (P = .048). Finally, there was significant agreement between the presence of fibrostenotic criteria and a long disease duration (P = .027). CONCLUSION: MRE discloses disease activity and complications not apparent with other modalities and results in changes in therapeutic decisions. In addition to being used for diagnosis, MRE should be routinely used in the follow-up of CD patients.